WALKING AND DRAWING. OVERLAPPING TEACHING EXPERIENCES IN ARCHITECTURE - Guilherme, Pedro (2022)
The practice of architecture is an ethical and responsible act that implies a rigorous and wide knowledge of the site of intervention and of the relationships between people and the built or natural environment where the construction is to be designed. Besides other, more currently used, methodologies1 in the teaching of architecture, the authors propose and promote in their curricular units2 walking (walkscape) and drawing as investigating tools and instruments for the understanding and comprehension of the territory. The walk, sometimes a little errant and free, others more organized and rigorously oriented, allows the cognitive understanding of the territory, surpassing the knowledge of its physical, visible, and measurable dimensions. Drawing is used as a tool for investigation, research, analysis, and registry. In fact, when joined together, walking and drawing create a specific essential instrument of knowledge, not only intuitive, but also interpretive of the place. This specific instrument can produce new knowledge and innovation. We have gathered some evidence that shows this joint methodological strategy has two advantages: on the one it allows the student to better consolidate his conceptual strategies and on the other hand, it allows the student to discover himself and his potential role within the territory.